When 2–3% really matters: The (un)importance of religiosity in psychotherapy - McVittie, Chris (Mental health, religion & culture, 2007)
Previous research suggests that clients’ religious beliefs are commonly excluded from therapeutic practice. Often, this exclusion is attributed to practitioners’ lack of knowledge or appropriate skills. Such analyses, however, have little regard for the interactional aspects of the therapist/client encounter. Drawing upon work within discursive social psychology, we argue that the exclusion of religious beliefs does not reflect therapists’ lack of knowledge or awareness but can more usefully be seen as the discursive accomplishment of marginalizing clients’ beliefs. Six practising psychotherapists were interviewed about religious beliefs within the therapeutic process. Participants construct religious beliefs as important but relevant only to restricted categories of clients. They rework religious beliefs as compatible with accepted practice, or construct particular groups of clients as incompatible with the process. Training and other requirements are reformulated in terms of spiritual beliefs rather than religious beliefs. These constructions display awareness of religious beliefs while marginalizing their relevance in practice. Inclusion of clients’ religious beliefs to best effect will require more psychotherapy to engage more constructively with religion than it does at present.